Finance for Renewable Energy: An Empirical Analysis of Developing and Transition Economies - Christa N. Brunnschweiler (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
This paper examines the role of the financial sector in renewable energy (RE) development. Although RE can bring socio-economic and environ- mental benefits, its implementation faces a number of obstacles, especially in non-OECD countries. One of these obstacles is financing: underdevel- oped financial sectors are unable to efficiently channel loans to RE produc- ers. The influence of financial sector development on the use of renewable energy resources is confirmed in panel data estimations on up to 119 non- OECD countries for 1980-2006. Financial intermediation, in particular commercial banking, has a significant positive effect on the amount of RE produced, and the impact is especially large when we consider non- hydropower RE such as wind, solar, geothermal, and biomass. There is also evidence that the adoption of the Kyoto Protocol has had a significant positive impact on the development of the RE sector.
Keywords: O13; O16; 330; renewable energy; financial sector; banking; development; Förderung erneuerbarer Energien; Finanzierung; Unternehmensfinanzierung; Finanzsektor; Entwicklungsländer; Transformationsstaaten